Analysis of the Effect of Labor Force, Exchange Rate, Foreign Direct Investment, and Export of Goods and Services on Gross Domestic Product in 6 ASEAN Countries - Istiqomah, Ratna; Faridatussalam, Sitti Retno (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: Several elements influence the growth rate of GDP are closely related to maintain social and political stability. This study aims to scrutinize the effect of Labor Force, Exchange Rate, Foreign Direct Investment, and Export of goods and services on Gross Domestic Product in 6 ASEAN countries. Methodology: This research was obtained from official website of worldbank.org and utilized secondary data. Analysis of data and hypothesis testing was carried out using the Panel Data Regression Method and the Fixed Effect estimation model through the Eviews 10 program. The sample of this study is panel data with a period of 2014-2021 and the countries included in this study are 6 countries, namely Indonesia, Malaysia, Singapore, Thailand, Philippines and Vietnam. Results: In partial, the analysis indicate that the Labor Force, Foreign Direct Investment, and Export of Goods and Services had a positive and significant influence on Gross Domestic Product. Meanwhile, Exchange Rate showed a negative and insignificant influence on Gross Domestic Product. Simultaneously, the Labor Force, Exchange Rate, Foreign Direct Investment, and Export of goods and services had a significant effect on Gross Domestic Product in 6 ASEAN countries, with a coefficient of determination of 99,22%. Applications/Originality/Value: Based on these results, it is recommended to optimize Labor Force, Foreign Direct Investment, and Export. In addition, it is necessary to maintain the steadiness of the Exchange Rate and analyze solutions in the face of current economic obstacles. It is also necessary to increase economic growth, so the government and stakeholders are responsible and repair to macroeconomic impacts.